ANALISA POROSITAS BETON BERPORI BERBASIS ZEOLIT ALAM PAHAE DAN KARBON AKTIF KULIT COKLAT - Sabda wahyuna; Fynnisa Z; Muhammad Irwansyah (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
Porous concrete is concrete that has cavities in its structure so that water can drain. The aim of this research is to obtain compressive strength and porosity referring to the Aci 522R-10 method using a cylindrical mold measuring 15 cm x 30 cm with a soaking age of 28 days. The highest compressive strength values ​​were obtained in porous concrete specimens mixed with 10% brown shell with an average compressive strength value of 11.7 Mpa and porous concrete mixed with 5% zeolite with an average compressive strength of 11,6 Mpa. The lowest compressive strength of porous concrete mixed with 5% zeolite + 10% brown skin with an average compressive strength of 5.5 Mpa and concrete mixed with 10% zeolite + 5% brown skin with an average compressive strength of 5,9 Mpa. The highest porosity was obtained in the 10% zeolite mixture variation test object and the 5% zeolite mixture + 5% brown leather variation test object, namely 27,6%.